Building Knowledge, Negotiating Expertise: Participatory Water Supply Advocacy and Service in Globalizing Jakarta. Issue 1 (1st March 2017) - Padawangi, Rita
Abstract : Urban water supply is a domain of expertise for which "best practices" have been dominated by states and financial institutions that are directly involved in infrastructure building. This leads to the implementation of decontextualized ideas and a transfer of knowledge from one place to another. Current urban water supply challenges and the social and cultural values of water are the background of this article to examine the role of participatory approaches in building knowledge and expertise in urban water management. This article asks three questions: (1) How does community participation help maintain water management in a particular neighborhood? (2) How does participation contribute to water accessibility in the long term? (3) How do these participatory efforts interact with the mainstream expertise and knowledge building in urban water management? It explores the main topic and these three questions with Jakarta as a case study. Specific attention is given to the experiences of urban poor communities in Jakarta in conducting participatory approaches for the provision and distribution of water, because problems in accessing safe drinking water are often most obvious in poor neighborhoods of the city. Embedded in the analysis is the discussion of the democratization of expertise in urban infrastructure. The case study shows that rather than challenging the dominant urban water management discourse, community participation coexists with the state and the private sector and coshapes the understandings of water expertise in the city. Through service-oriented participation and advocacy-oriented participation, communities could build knowledge and negotiate expertise about water management through their experiences. However, at the moment it is still unlikely that these participatory approaches would challenge the dominant urban water management paradigm.